Unsolicited dick pics: Erotica, exhibitionism or entitlement? - Hayes, Rebecca M.; Dragiewicz, Molly (Women's studies international forum, 2018)
Technologically mediated forms of sexual abuse have been the subject of extensive media discussion in the 2000s. Arguably, digital media have transformed sexual abuse. Cultural anxieties around sexting and revenge porn have been accompanied by an emerging body of scholarly literature on image-based sexual abuse and harassment. Concern with image-based sexual abuse has centered on the non-consensual distribution of private nude images of women and girls via digital media, which is often represented as harmful, dangerous for the woman or girl in the image, and potentially criminal. Conversely, scholars have just begun to turn their attention to men's intentional distribution of unsolicited images of their penises to women. In this article, we consider the theoretical concepts of the continuum of sexual violence and sexual and aggrieved entitlement alongside the interdisciplinary literature on image-based sexual abuse, sexual harassment, and exhibitionism to propose a future research agenda for understanding the contemporary phenomenon of men sending unsolicited dick pics to women. We argue that dick pics merit scholarly attention as an emerging cultural practice.